2021
DOI: 10.1038/s41419-021-04236-z
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-PFAR facilitates autophagy and exacerbates pancreatic fibrosis by reducing pre-miR-141 maturation in chronic pancreatitis

Abstract: Chronic pancreatitis (CP) is described as progressive inflammatory fibrosis of pancreas, accompanied with irreversible impaired endocrine and exocrine insufficiency. Pancreatic stellate cells (PSCs) are widely distributed in the stroma of the pancreas and PSCs activation has been shown as one of the leading causes for pancreatic fibrosis. Our previous study has revealed that autophagy is dramatically activated in CP tissues, which facilitates PSCs activation and pancreatic fibrosis. Long non-coding RNAs (LncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Chronic hyperglycemia can activate PSCs and promote the interaction between PSCs and pancreatic cancer cells ( 10 ). Activated PSCs play a crucial role in the development of pathological pancreatic fibrosis ( 11 , 12 ), which characterizes chronic pancreatitis ( 13 , 14 ) and pancreatic cancer-associated desmoplastic reaction ( 7 , 15 ). Therefore, chronic pancreatitis and pancreatic cancer can be treated using anti-fibrotic agents, such as vitamin analogs, targeting PSCs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hyperglycemia can activate PSCs and promote the interaction between PSCs and pancreatic cancer cells ( 10 ). Activated PSCs play a crucial role in the development of pathological pancreatic fibrosis ( 11 , 12 ), which characterizes chronic pancreatitis ( 13 , 14 ) and pancreatic cancer-associated desmoplastic reaction ( 7 , 15 ). Therefore, chronic pancreatitis and pancreatic cancer can be treated using anti-fibrotic agents, such as vitamin analogs, targeting PSCs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…TGFĪ² signaling plays an essential role in activating PSCs during CP via induction of expression of several matrix metalloproteinases and tissue inhibitors of metalloproteinases, resulting in extracellular matrix remodeling, deposition of collagen fibers, and increased stiffness of the tissues. Zhang et al demonstrated that TGFĪ² increases lnc-PFAR levels, which then binds to premature miR-141-5p, blocks its maturation, and activates fibrosis and autophagy in PSCs [ 119 ] ( Figure 6 ). Furthermore, miR-141-5p prevents autophagy by binding to 3ā€²UTR of Retinoblastoma coiled-coil protein 1, inhibiting ULK1 dephosphorylation and reducing autophagy.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…However, in CP, the levels of miR-141-5p are downregulated, and thus, the fibrosis and autophagy of PSCs are increased. Importantly, in vivo studies showed that delivery of lnc-PFAR enhanced fibrosis in CP, as shown by H&E and Massonā€™s Trichrome stains, on molecular markers of fibrosis such as fibronectin, collagen I/III, and Ī±-SMA [ 119 ].…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…Autophagy is a cellular process in degrading of long-lived proteins and organelles and misfolded proteins in the cytosol for maintaining cellular homeostasis, which has been linked to many states of human health and disease ( Xu et al, 2018 ; Zhang et al, 2021 ). Recently, VD has been demonstrated to alleviate ethanol-induced hepatotoxicity by enhancing autophagy ( Yuan et al, 2021 ).…”
Section: Mechanisms Of Vitamin D Action In Chronic Pancreatitismentioning
confidence: 99%
“…Additionally, inhibiting autophagy can also suppress pancreatic fibrosis through promoting ECM degradation by decreasing the expression of TGF-Ī²1 and increasing MMPs/TIMPs ratio ( Li et al, 2018a ). Retinoblastoma coiled coil protein 1-induced autophagy can facilitate PSC activation and pancreatic fibrosis in CP ( Li et al, 2018c ; Zhang et al, 2021 ). Contrarily, PDGF inhibits autophagy in HSC and increases the release of extracellular vesicle (EV) ( Gao et al, 2020 ), while the release of EV can promote the interaction between cells and fibrosis ( Xu et al, 2018 ), suggesting that autophagy in HSC alleviated liver fibrosis by reducing the release of HSC-derived EV ( Gao et al, 2020 ).…”
Section: Mechanisms Of Vitamin D Action In Chronic Pancreatitismentioning
confidence: 99%